Online political trust in Anies Baswedan and Ganjar Pranowo: Who is the new potential candidate? - Tawakkal Baharuddin (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
Political trust has long been one of the indicators to assess whether the democratic system is running stable. This study seeks to develop this idea with new discussions, particularly the assessment of online political trust, by focusing on cases related to the 2024 Indonesian Presidential Election issue, which raised the names of potential new candidates in the regional elections. The identified candidates are Anies Baswedan and Ganjar Pranowo. This study used a quantitative approach with descriptive content analysis. Data collection is carried out based on the candidate's official account on Twitter and other relevant information. This study relies on the Nvivo 12 Plus analysis tool. This study found that political trust can be legitimized through online social networks such as social media. Anies Baswedan emerged as the dominant candidate influencing online political trust on Twitter. The high results of public discussion significantly affect the increase in trust in candidates who are often mentioned and popular on social media. Another dominant factor that influences is the online activity of the candidates. This study found the relevance of online political trust for candidates and democracy, namely determining the electability of candidates, elections, and political participation. Online political trust is increasingly important in the context of politics and democracy. In cyberspace, people access much information about political issues, which often shapes their political views and trust. The findings of this study also confirm that online political trust can be an essential indicator for assessing the progress of digital democracy in the future.